A new design method for a dual band branch line hybrid coupler (Mongolian Journal of Agricultural Sciences, 2015)
This paper presents the design of a dual band branch line hybrid coupler (BLHC) with different power division ratios at two bands. In the proposed design, transmission lines of the BLHC are transformed to